2004
DOI: 10.1523/jneurosci.5544-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Stress Enables Synaptic Depression in CA1 Synapses by Acute and Chronic Morphine: Possible Mechanisms for Corticosterone on Opiate Addiction

Abstract: The hippocampus, being sensitive to stress and glucocorticoids, plays significant roles in certain types of learning and memory. Therefore, the hippocampus is probably involved in the increasing drug use, drug seeking, and relapse caused by stress. We have studied the effect of stress with morphine on synaptic plasticity in the CA1 region of the hippocampus in vivo and on a delayed-escape paradigm of the Morris water maze. Our results reveal that acute stress enables long-term depression (LTD) induction by low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 85 publications
10
71
1
1
Order By: Relevance
“…3 A, B, and E). Although prolonged low-frequency stimulation (LFS; 1 Hz for 15 min) does not induce LTP or LTD in adult rats (26,31,45,46), we found that LFS induced a small LTP in WT mice but not in CKO mice (Fig. 4 A, B, and E).…”
Section: Cko Mice Show Fast Acquisition and Enhanced Fearmentioning
confidence: 68%
“…3 A, B, and E). Although prolonged low-frequency stimulation (LFS; 1 Hz for 15 min) does not induce LTP or LTD in adult rats (26,31,45,46), we found that LFS induced a small LTP in WT mice but not in CKO mice (Fig. 4 A, B, and E).…”
Section: Cko Mice Show Fast Acquisition and Enhanced Fearmentioning
confidence: 68%
“…LTD is an electrical correlate of the weakening of the connection between two neurons, thus leading to long-term reduction in the efficacy of neuronal synapsis as a consequence of a decrease in the density of postsynaptic receptors. Studies have shown that both acute and chronic stress [Yang et al, 2004;Holderbach et al, 2007], including exposure to predators [Kuzmiski et al, 2010;Kim and Diamond, 2002], can lead to LTD. LTD has also been associated with synaptic plasticity and memory formation [Bear, 1999;Malleret et al, 2010;Kim and Diamond, 2002]. Importantly, our study also identified many genes and biological pathways that have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with stressful events provokes neuroendocrine responses as well as changes in neurotransmitter systems (Koob, 2006), and drug abuse is related to neurobiological responses to stress, including the release of the glucocorticoid stress hormone corticosterone (Martinelli and Piazza, 2002;Yang, et al, 2004;Le et al, 2005), and changes in monoamine neurotransmitter activity (Heinz et al, 2002;Kalivas and McFarland, 2003;Zhang and Kosten, 2005;Salomon et al, 2006;Sorge and Stewart, 2005). This section reviews evidence that sign-tracking procedures induce changes in corticosterone levels and monoamine neurotransmitters that resemble the stressrelated responses known to accompany alcohol and drug abuse.…”
Section: Stress-related Effectsmentioning
confidence: 99%